A green route for pyrolysis poly-generation of typical high ash biomass, rice husk: Effects on simultaneous production of carbonic oxide-rich syngas, phenol-abundant bio-oil, high-adsorption porous carbon and amorphous silicon dioxide. (January 2020) - Su, Yinhai; Liu, Lingqin; Zhang, Shuping; Xu, Dan; Du, Haoran; Cheng, Yu; Wang, Zhongwen; Xiong, Yuanquan
Graphical abstract: Highlights: Poly-generation of rice husk was realized for four end products. Relative content of phenol was 65.56% in bio-oil. Syngas contained CO of 56.09 vol%. Acid washing benefits both pore structure and surface functional groups of biochar. A low-cost porous carbon with high absorption was obtained after SiO2 extraction. Abstract: Rice husk is a widespread agriculture waste in rice-farming country. High silica content in rice husk prevent its efficient utilization. So in this work, concept of poly-generation was introduced to improve its utilization value. This study provided CO-rich syngas, phenol-abundant bio-oil, high-adsorption porous carbon and amorphous SiO2 as four end products for first time via combination of acid washing and activated carbon catalyst. Specifically, acid washing effectively decreased soluble ash, which altered pyrolysis paths, increased volatiles release and reduced impurities in bio-char. After catalytic pyrolysis, phenol content of 65.56% and CO of 56.09 vol% were detected in bio-oil and syngas from AWRH. For solid products, acid washing benefited both bio-char and silica. A low-cost porous carbon with developed pores and rich surface functional groups was prepared for water absorption. And high purity amorphous SiO2 was recycled from alkali etching solution. Finally, a green process with no waste emission was proposed.